Institutos de direito do trabalho aplicados na sustentabilidade do terceiro setor - Camargos, Ana Amélia Mascarenhas (2005)
The work evidences the importance of the work conducted by the third sector to developing countries such as Brazil as the State has been scaling back its social services In this regard it reviews and defines those entities making up the third sector and analyzes some labor law instruments by relating them to not-for-profit organizations\' increased activities By studying topics such as persons with disabilities work conducted by minors, social cooperatives profit-sharing for employees of third sector organization voluntary and religious work this work demonstrates the importance of the third sector in labor laws and how such power can be used to enhance those activities performed by this sector, as well as social actions designed to include disadvantaged persons